Conocimientos y actitudes frente a la donación de órganos y tejidos en estudiantes de enfermería de la UNT - 2016 - Cruz Saavedra, Maryori Luceli (2016)
Research correlational descriptive and cross-section was performed on nursing students from the National University of Trujillo, in order to determine the relationship between the level of knowledge and attitude of students towards the donation of organs and tissues. The universe consisted of 116 students who met the inclusion criteria, who were applied two instruments: questionnaire to determine the level of knowledge and scale to determine the attitude about organ and tissue donation. The results are presented and interpreted in tables of single and double entry, as well as statistical graphs. For the statistical analysis Chi Square test was used and reached the following conclusions: 69.8% of students presented a medium level of knowledge about organ and tissue donation; 25.9% had a high level of knowledge and 4.3% had a low level of knowledge; regarding attitudes toward organ and tissue donation, 76.6% of students, present attitude of acceptance and 23.3% present attitude of indifference. highly significant relationship between the level of knowledge and attitude about organ donation and tissue was found. (P=0.00958<0.01)